Pediatric Status Epilepticus Severity Score (STEPSS): Predictive Performance of Functional Outcomes: A Prospective Single-Center Study. (December 2022) - Soydan, Ekin; Gonullu, Ahmet; Aksoy, Yigit; Guzin, Yigithan; Ceylan, Gokhan; Topal, Sevgi; Colak, Mustafa; Hepduman, Pınar; Sandal, Ozlem Sarac; Atakul, Gulhan; Karaarslan, Utku; Unalp, Aycan; et al.
Objective: To prospectively investigate the predictive value of the modified Status Epilepticus Severity Score (STESS) for pediatric use (STEPSS) regarding unfavorable outcomes in the short term.Methods: Patients diagnosed as status epilepticus in the emergency department between January 2019 and June 2021 at a tertiary center of the University of Health Sciences, Dr. Behcet Uz Children's Hospital, were included in the study. The patients were followed up in the emergency department, neurology clinic, and pediatric intensive care unit until discharge. Demographic and clinical characteristics, STEPSS, and Pediatric Overall Performance Category Scale (POPC) scores were calculated. We defined a Pediatric Overall Performance Category Scale score ≥3 as an unfavorable outcome. We compared the effect of STEPSS on unfavorable outcomes and mortality.Results: 124 children were included. The median age was 33 months (interquartile range 16.2-84.7). Seventy-two (58.1%) patients had acute symptomatic etiology. We found that the STEPSS score with the receiver operating characteristic curve (area under the curve  = 0.917, P  < .001) could predict unfavorable outcomes (Pediatric Overall Performance Category Scale score ≥3) in children with status epilepticus. The Youden index (0.76) showed that a STEPSS score >2 was the optimal cutoff point for an unfavorable outcome. We found STEPSS useful in predicting mortality (area under the curve  = 0.853, P  < .001). The Youden index (0.58) indicated that a STEPSS >2 was the optimal cutoff for mortality: sensitivity 0.90 (95% confidence interval [CI] 0.58-0.99), specificity 0.67 (95% CI 0.57-0.77), positive predictive value 0.21, negative predictive value 0.98, positive likelihood ratio 2.7, negative likelihood ratio 0.14.Conclusion: We determined that STEPSS can be predicted unfavorable outcomes and mortality. We think that STEPSS can be used as a useful clinical score with further studies and external validations.